STRATEGIC DIRECTIONS FOR INCREASING THE ATTRACTIVENESS OF INVESTMENT PROJECTS AND ATTRACTING FOREIGN CAPITAL IN THE REPUBLIC OF UZBEKISTAN (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This analytical article systematically studies the mechanisms for attracting foreign direct investment (FDI) to the economy of the Republic of Uzbekistan in the context of globalization and international economic integration, the existing investment environment, and the effectiveness of structural reforms. The article provides a detailed analysis of the leading partner countries investing in the national economy, the distribution of capital across sectors and regions, as well as the asymmetric situation of free economic zones in absorbing investments. In order to further increase the investment attractiveness of the republic, practical proposals are put forward to improve the regulatory framework, reduce bureaucratic barriers, digitize infrastructure, and activate the international investment branding and marketing strategy.